2009
DOI: 10.1016/j.biopsycho.2008.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Listeners modulate temporally selective attention during natural speech processing

Abstract: Spatially selective attention allows for the preferential processing of relevant stimuli when more information than can be processed in detail is presented simultaneously at distinct locations. Temporally selective attention may serve a similar function during speech perception by allowing listeners to allocate attentional resources to time windows that contain highly relevant acoustic information. To test this hypothesis, event-related potentials were compared in response to attention probes presented in six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
81
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 51 publications
10
81
1
Order By: Relevance
“…This may have to do with the fact that the magnitude of brain responses, i.e., ERPs to T5 rise time and MMN amplitude lack a speed component, and thus have less in common with one's efficiency of allocating attentional resources. The current findings of contribution of attention to speech processing are compatible with our previous study where visual attention switching could predict tone discrimination efficiency (Ou et al, 2015), as well as research that also found a role of attention in modulating perceptual sensitivity to speech sounds (e.g., Astheimer & Sanders, 2009;Díaz et al, 2008;Jesse & Janse, 2012). The significance of attention switching/ shifting in influencing the distinctiveness of speech representations has been hypothesized in the SAS hypothesis (Hari & Renvall, 2001;Lallier et al, 2010;Ruffino et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…This may have to do with the fact that the magnitude of brain responses, i.e., ERPs to T5 rise time and MMN amplitude lack a speed component, and thus have less in common with one's efficiency of allocating attentional resources. The current findings of contribution of attention to speech processing are compatible with our previous study where visual attention switching could predict tone discrimination efficiency (Ou et al, 2015), as well as research that also found a role of attention in modulating perceptual sensitivity to speech sounds (e.g., Astheimer & Sanders, 2009;Díaz et al, 2008;Jesse & Janse, 2012). The significance of attention switching/ shifting in influencing the distinctiveness of speech representations has been hypothesized in the SAS hypothesis (Hari & Renvall, 2001;Lallier et al, 2010;Ruffino et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…On the contrary, TP computation relies on a domain-general learning mechanism (e.g., Fiser & Aslin, 2001;Perruchet & Pacton, 2006;Turk-Browne et al, 2005) that may be more sensitive to attention resources and hence to cognitive load. A recent study by Astheimer and Sanders (2009) also suggests that domain specificity could play a role in the allocation of selective attention to word onsets. In their study, whereas linguistic, and hence speech-specific, probes (e.g., the syllable "ba") were able to modulate listeners' selective attention to word onsets in a continuous speech flow, no impact of general auditory, nonlinguistic probes (i.e., pure tones) was found.…”
Section: General R R Discussionmentioning
confidence: 99%
“…Only a few had addressed the impact of cognitive load on speech processing, and rather indirectly (e.g., Jacquemot, Dupoux, Decouche, & Bachoud-Lévi, 2006;Mirman, McClelland, Holt, & Magnuson, 2008; see also Astheimer & Sanders, 2009). In Mattys et al's (2009) study, severe energetic masking decreased reliance on lexical-semantic knowledge and increased reliance on acoustic detail-namely, on acoustic cues linked to coarticulation.…”
Section: Methodsmentioning
confidence: 99%
“…Learning a second language requires focusing on the relevant aspects of the new language, ignoring distractions, and suppressing interference from the non-target language (see Bialystok, 2001 for a review). Furthermore, speech is a perceptually complex stimulus that contains rapidly changing acoustic information; executive processes might be used to determine which of the overwhelming amount of sensory information needs to be processed in greater detail (Astheimer & Sanders, 2009). Children with better executive processes may therefore present an advantage in second language learning.…”
mentioning
confidence: 99%